Factors affecting FDI in Singapore - Mak, Yi Ling; Poah, Yi Wern; Leong, Roger Xeyn Roong; Yong, Jun Xian (2022)
The aim of the study is to investigate the relationship between the foreign direct investment (FDI) and the inflation rate, trade openness, economic growth and exchange rate. In this research, the secondary data was being collected from World Bank and the period being used was 1985 to 1969. First Augmented Dickey Fuller (ADF) test and Phillips-Perron (PP) test was carried out to examine the stationarity of the data. Following that, Johansen Methodology is used to determine the cointegration of the model and to examine the long-run equilibrium relationship of the variables. Then, the Vector Error Correction Model (VECM) and Granger Causality test was carried out in this research. The result shown that the all the factors does not granger cause the FDI. However, FDI so show Granger causality to some of the factors such as economic growth and trade. Meanwhile, we use macroeconomics variables in this research and the result shown that FDI does not granger cause the macroeconomic variables.